The role of love in public sector leadership in Slovenia - Pličanič, Senko (Array, 2021)
The article discusses the importance of self-love in public sector leadership and public sector employees engagement. Given the importance of leadership in our civilisation, the almost complete absence of self-love in leaders is especially detrimental to the organisations they lead and their employees. This is especially important in the public sector–due to the importance of the goods and services it provides, and the fact that it does so with the taxpayers’ money. Leaders who love themselves and lead with love, know how to step into the employees’ shoes, understand them; know how to find the best in each one of them and encourage the development of that aspect; they are sincere and warm; know how to listen to employees and impress them; they are respectful of them; they inspire a sense of security and confidence; spread positive energy and know how to make decisions.Also, the connection between self-love and sustainable development social model is discussed. Due to the unilateral orientation of our civilisation toward material development, individuals have almost eliminated the pursuit of spiritual development from their lives. However, love and happiness can only be achieved with the balance of both. The integral principle of sustainable development, which, in addition to economic growth, encompasses spiritual growth, is a model that offers us a way out of our (bad) state–in the world and in Slovenia. Of particular importance–primarily because of the long absence–is the spiritual side. People need to reintroduce it into their lives. In doing so, the state and the law should be “utilised”, and to set as their main task the provision of conditions for (in addition to economic) spiritual growth and thus love and happiness.